Formula of Superhero In Black Panther by Ryan Coogler - Sisca Ayu Ningsih (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2018)
This study aims to analyze the formulas of convention and invention in the film â€œBlack Pantherâ€. The problem in this study is what are the new superhero formulas that appear in the Black Panther film. The research method is the qualitative method. Theory Formula from John G. Cawelti's is used to analyze the data. The objective is to describe the superhero formula that appears in the Black Panther film by Ryan Coogler. The data was collected through watching the film, identifying and cataloging. While the technique of data analysis, namely describing, analyzing, interpreting and concluding. This study found new formulas in the Black Panther film, such as; (1) the main character is black, (2) the antagonist has a clear motive, (3) takes place in Africa, (4) the female character is very tough and smart, (5) shows a lot of culture African.